Hologram guided target designation. - Nasrullah, K.; Juliana , M
A passive hologram guided target designation is more superior than simple matrix or image guided system due to its three-dimensional target acquisition and recognition. To implement this criterion a target hologram was loaded into onboard optics that was a part of a dynamic scanning system. The observed data was compared with onboard target hologram and found that the system accuracy was better than the conventional systems. To make the carrier invisible multi-layer coating were used that resulted in perfect concealing of the carrier. Once the target acquisition is complete the locking system stops further comparison and reorientates the canter direction on to the target. This paper critically overviews general principles involved and experimental furtherance in the field of optically guided target designators. There is say that a perfect control of the electromagnetic spectrum can close the eyes or ears and renders the defense blind and deaf. Normally laser and fiber optic guided missiles are more popular than the conventional guided missiles but our proposed hologram guidance approach is likely to establish its own technical distinct and novelty.